Răspuns :
Explicație pas cu pas:
- a= {[(2^4)^3:(2^2)^2×(2^6)^2]^2:(2^8)^4}^6: (2^23)^2
- = [(2^12:2^4×2^12)^2:2^32]^6: 2^46
- =[(2^12-4+12)^2:2^32] ^6: 2^46
- =[(2^20)^2:2^32] ^6: 2^46
- =(2^40÷2^32)^6÷2^46
- =(2^8)^6÷2^46
- =2^48÷2^46
- =2^2
- =4 => a€N
b ={[(3/2)^3]^10:[(-2/3)^4]^6×(9/4)^2}^4:(3/2)^38×4
- =[(3/2)^30:(2/3)^24×(3/2)^4]^4:(3/2)^38×4
- =[(3/2)^30×(3/2)^24×(3/2)^4]^4:(3/2)^38×4
- =[(3/2)^6×(3/2)^4]^4:(3/2)^38×4
- =[(3/2)^10]^4:(3/2)^38×4
- =(3/2)^40:(3/2)^38×4
- =(3/2)^2×4
- =9/4×16/4
- =144/16
- =9 =>b€N
a=4=2^2=p.p
b=9=3^2=p.p.
Obs. am folosit semnul ^ pt puteri : a^b( și se citeste a la puterea b)
Sper ca team ajutat !